Electronic Beehive Weights - Mička, Josef; Mareček, Jakub; Man, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The goal of this project was to create electronic beehive weights which will help to control progression of hives and to create an interface that will be able to show measured data in charts and graphs.
Keywords: mikrokontroler; webové rozhraní; API; GSM; Raspberry Pi